Diagnostic value of preoperative axillary lymph node ultrasound assessment in patients with breast cancer qualified for sentinel lymph node biopsy - Nowikiewicz, Tomasz (Wideochir Inne Tech Maloinwazyjne, 2015)
INTRODUCTION: Sentinel lymph node biopsy (SLNB) is a standard procedure in the therapeutic management of patients with non-advanced breast cancer. AIM: To analyse the utility of ultrasound scan (USS) examination in the process of patient qualification for SLNB and to estimate the optimal time to perform USS in the clinical preoperational assessment of axillary lymph nodes. MATERIAL AND METHODS: A prospective analysis of 702 patients with invasive breast cancer treated with SLNB between 7.03.2012 and 27.05.2013 was performed. The patients were divided into three groups: I (USS < 8 weeks before SLNB), II (USS > 8 weeks before SLNB and another one on the day before SLNB) and III (USS > 8 weeks before SLNB without perioperative USS). In these patients the percentage of metastases in the sentinel lymph node and the clinical factors influencing the diagnostic value of preoperative ultrasound scan were assessed. RESULTS: Metastatic lesions in sentinel lymph nodes were found in 154 (21.9%) patients. The highest percentage of metastases was noted in patients operated on in the second and third month from the beginning of preoperative diagnostics. None of the factors tested (size of the original tumour, histological malignancy grading, kind of preoperative diagnostics, Ki-67 value, biological type of the tumour, age) had a statistically significant influence on the diagnostic value of perioperative USS examination in the analysed time span. CONCLUSIONS: The lowest percentage of metastases in the sentinel lymph node was noted in the patients qualified for SLNB who had the ultrasound performed directly before the surgical procedure (not more than 4 weeks before the surgery).